A cross-sectional analysis of the association between self-employment, racial and ethnic minority status, sex and cardiovascular disease risk factors among a nationally representative sample - Kimberly Narain; Daniela Markovic; José J. Escarce (BMC Public Health)
Abstract Background There is a body of evidence that suggest risk factors for cardiovascular disease (CVD) may be linked with self-employment status. Work context varies across race, ethnicity and sex. The objective is to examine the association of self-employment status and CVD risk factors across racial and ethnic minority status as well as sex. Methods For this observational study, National Health and Nutrition Examination Survey (NHANES) data (1999–2018), a cross-sectional study design, and stratified logistic regression models were used to explore the association between self-employment status (a dichotomous variable) and CVD risk factors (dichotomized measures of elevated cholesterol, hypertension, glucose intolerance, obesity, poor diet, physical inactivity, smoking, binge drinking, sub-optimal sleep duration and poor mental health) across combined racial and ethnic minority status and sex groups, among working, non-pregnant adults(ages 30–62). Statistical models controlled for age, education, marital status, household poverty-to-income ratio, and the number of months working at current job. The coefficient estimates were expressed as predictive margins. Results The study sample was comprised of 19,395 working adults. Among non-minority women, self-employment was negatively associated with obesity (% diff = -7.4%; p = 0.008), physical inactivity % diff = -7.0%; p = 0.017), and poor sleep duration (% diff = -9.4%; p = 0.004). Among minority women, self-employment was negatively associated with poor diet (% diff = -6.7%; p = 0.024), physical inactivity (% diff =-7.3%; p = 0.013) and poor sleep duration (% diff = -8.1%; p = 0.017). Among non-minority men, self-employment was negatively associated with poor diet (% diff = -6.5%; p = 0.008) and hypertension (% diff = -5.7%; p = 0.013). Conclusions This study suggests that there may be a relationship between work context and CVD risk factors that varies across race, ethnicity and sex; however, further research is needed to characterize this relationship. Specifically, exploring how autonomy, flexibility, social support and discrimination exposure varies across self-employment status in diverse demographic groups may be important for illuminating the relationship between work and cardiovascular health.